Nanog Increases Focal Adhesion Kinase (FAK) Promoter Activity and Expression and Directly Binds to FAK Protein to Be Phosphorylated - Ho, Baotran (American Society for Biochemistry and Molecular Biology, 2012)
Nanog and FAK were shown to be overexpressed in cancer cells. In this report, the Nanog overexpression increased FAK expression in 293, SW480, and SW620 cancer cells. Nanog binds the FAK promoter and up-regulates its activity, whereas Nanog siRNA decreases FAK promoter activity and FAK mRNA. The FAK promoter contains four Nanog-binding sites. The site-directed mutagenesis of these sites significantly decreased up-regulation of FAK promoter activity by Nanog. EMSA showed the specific binding of Nanog to each of the four sites, and binding was confirmed by ChIP assay. Nanog directly binds the FAK protein by pulldown and immunoprecipitation assays, and proteins co-localize by confocal microscopy. Nanog binds the N-terminal domain of FAK. In addition, FAK directly phosphorylates Nanog in a dose-dependent manner by in vitro kinase assay and in cancer cells in vivo. The site-directed mutagenesis of Nanog tyrosines, Y35F and Y174F, blocked phosphorylation and binding by FAK. Moreover, overexpression of wild type Nanog increased filopodia/lamellipodia formation, whereas mutant Y35F and Y174F Nanog did not. The wild type Nanog increased cell invasion that was inhibited by the FAK inhibitor and increased by FAK more significantly than with the mutants Y35F and Y174F Nanog. Down-regulation of Nanog with siRNA decreased cell growth reversed by FAK overexpression. Thus, these data demonstrate the regulation of the FAK promoter by Nanog, the direct binding of the proteins, the phosphorylation of Nanog by FAK, and the effect of FAK and Nanog cross-regulation on cancer cell morphology, invasion, and growth that plays a significant role in carcinogenesis.